Sciatica from a Foraminal Lumbar Root Schwannoma: Case Report and Review of Literature - Tarush Rustagi; Siddharth Badve; Aseem N. Parekh (Case Reports in Orthopedics)
Sciatica is commonly caused by lumbar prolapsed intervertebral disc (PID) and other spinal lesions. Uncommon causes like nerve root schwannoma are rarely considered in the differential diagnosis of sciatica. Spinal schwannomas occur both sporadically and in association with neurofibromatosis type 1 (NF1; von Recklinghausen's disease). This case report describes lumbar foraminal schwannoma as an unusual cause of radiculopathy, presenting clinically as a lumbar disc prolapse. The diagnosis was confirmed on MRI scan. Patient had complete symptomatic recovery following surgical enucleation of the tumour mass from the L5 nerve root. This case report is of particular interest as it highlights the diagnostic confusion, which is bound to arise, because the clinical presentation closely mimics a lumbar PID. This often leads to delay in diagnosis and “failure of conservative treatment.”